A new technique of leak detection in a gas pipeline network based on time reversal method and non linear acoustic - Ghazali, M. F.; Yusof, Mohd Fadhlan M.; Baharom, Mohamad Zairi; Nizwan, Che Ku Eddy; Abdullah, Arman; Priyandoko, Gigih (2013)
This research seeks a new leak detection method based on time reversal wave propagation and acoustics – two recent most promising developments from the area of physical acoustics i.e time reversal and acoustics. The proposed method attempts to use the so-called nonlinear effect for leak detection in water pipelines. At the end of the research, the propose method is expected to identify features such as leak that present on the pipeline system even on complicated pipeline arrangements with strong noise. Furthermore, comparison with other method approaches will be performed to determine the credibility of the proposed method.